Lipidomic analysis of plasma, erythrocytes and lipoprotein fractions of cardiovascular disease patients using UHPLC/MS, MALDI-MS and multivariate data analysis - Holčapek, Michal; Červená, Blanka; Cífková, Eva; Lísa, Miroslav; Chagovets, Vitaliy; Vostálová, Jitka; Bancířová, Martina; Galuszka, Jan; Hill, Martin (Journal of chromatography. B, Analytical technologies in the biomedical and life sciences, 2015)
Differences among lipidomic profiles of healthy volunteers, obese people and three groups of cardiovascular disease (CVD) patients are investigated with the goal to differentiate individual groups based on the multivariate data analysis (MDA) of lipidomic data from plasma, erythrocytes and lipoprotein fractions of more than 50 subjects. Hydrophilic interaction liquid chromatography on ultrahigh-performance liquid chromatography (HILIC-UHPLC) column coupled with electrospray ionization mass spectrometry (ESI-MS) is used for the quantitation of four classes of polar lipids (phosphatidylethanolamines, phosphatidylcholines, sphingomyelins and lysophosphatidylcholines), normal-phase UHPLC-atmospheric pressure chemical ionization MS (NP-UHPLC/APCI-MS) is applied for the quantitation of five classes of nonpolar lipids (cholesteryl esters, triacylglycerols, sterols, 1,3-diacylglycerols and 1,2-diacylglycerols) and the potential of matrix-assisted laser desorption/ionization mass spectrometry (MALDI-MS) is tested for the fast screening of all lipids without a chromatographic separation. Obtained results are processed by unsupervised (principal component analysis) and supervised (orthogonal partial least squares) MDA approaches to highlight the largest differences among individual groups and to identify lipid molecules with the highest impact on the group differentiation.
Keywords: lidé; Middle Aged; Adult; kardiovaskulární nemoci; Obesity; Lipids; Lipidomics; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Multivariate Analysis; multivariační analýza; Chromatography, High Pressure Liquid; Humans; Computational Biology; obezita; výpočetní biologie; lidé středního věku; Lipoprotein fractions; kohortové studie; Cohort Studies; mužské pohlaví; Cardiovascular Diseases; vysokoúčinná kapalinová chromatografie; metoda nejmenších čtverců; lipidy; spektrometrie hmotnostní - ionizace laserem za účasti matrice; Least-Squares Analysis; Lipoproteins; Multivariate data analysis; Male; lipoproteiny; UHPLC/MS; dospělí; Cardiovascular diseases